Bionic polyether-ether-ketone dental implant material and preparation method thereof

Through the composite technology of multi-layer polyether ether ketone with glass fiber and modified materials, dental implants with changing neck to root gradient were prepared, solving the structural, functional and aesthetic mismatch of existing dental implant materials. Improves osseous binding and antibacterial properties and achieves a more stable transplantation effect.

CN119236184AActive Publication Date: 2025-01-03PEKING UNIV SCHOOL OF STOMATOLOGY

Patent Information

Application Number
CN202411375400.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-03
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

Existing dental implant materials cannot achieve structural, functional and aesthetic gradient bionics from the neck to the root, resulting in insufficient stress shielding and osseous binding, limiting their application in dental implants.

Method used

Using multi-layer polyether ether ketone combined with glass fiber and modified material, a dental implant with gradient change from neck to root is prepared by vacuum hot pressing technology, and its hydrophilicity is enhanced by biomodified material. and antibacterial properties.

Benefits of technology

The mechanical and aesthetic gradient from the neck to the root is achieved, the osseous binding effect and antibacterial performance are enhanced, and the stability and biological activity of the implant are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236184A_ABST
    Figure CN119236184A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of biomedical materials, in particular to a bionic polyether-ether-ketone dental implant material and a preparation method thereof. The preparation method of the bionic polyether-ether-ketone dental implant comprises the following steps: mixing polyether-ether-ketone, a modified material and glass fibers in ethanol, and drying to respectively obtain composite powder of the modified material and the glass fibers in gradient change; the preparation method comprises the following steps: respectively pressing glass fiber / modified material / polyether-ether-ketone composite powder with different contents into composite powder discs, then stacking layer by layer according to the sequence of the contents of the glass fiber materials from high to low and the sequence of the contents of the modified materials from low to high, and forming to obtain a composite material biscuit; and cutting the composite material biscuit by using CAD / CAM according to a designed implant model to obtain the bionic polyether-ether-ketone dental implant. The invention provides a precise bionic polyether-ether-ketone dental implant material which is gradually changed from neck to root mechanics and aesthetics and has osteogenesis promoting and antibacterial properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biomedical materials, and in particular to a bionic polyetheretherketone dental implant material and a preparation method thereof. Background Art

[0002] At present, pure titanium and titanium alloys are the most commonly used implant materials. Their advantages are good wear resistance, corrosion resistance, and cell and tissue compatibility. In addition to the implant field, they are also widely used in orthopedic implants. However, the elastic modulus of titanium and titanium alloys (110GPa) is significantly higher than that of human bones (0.02-20GPa), which does not match the elastic modulus of natural alveolar bones, resulting in stress shielding, which can easily lead to occlusal stress concentration in local areas, causing mechanical complications such as rapid absorption of the surrounding jawbone or implant fracture, leading to implant failure.

[0003] Polyetheretherketone (PEEK) is a high-performance engineering plastic. It is widely used in the medical field, especially in orthopedic and dental implants, due to its excellent mechanical properties, heat resistance and biocompatibility. PEEK has a similar elastic modulus to human bone, good mechanical properties, wear resistance and biocompatibility. It is an FDA-certified bio-implantable material and an ideal bone substitute. However, PEEK is a hydrophobic material with biological and chemical inertness, which has disadvantages in bone bonding, limiting its further application. Although the elastic modulus of PEEK implant material is similar to that of human bone, it has deficiencies in mechanical strength, biocompatibility and antibacterial properties, making it difficult to simultaneously meet the multiple needs of the complex oral environment. In addition, the natural alveolar bone gradually transitions from cortical bone to cancellous bone from crown to root, and the elastic modulus gradually decreases. The functions of implants in the vertical direction are different. The neck is the main part that bears the force, and it must match the elastic modulus of the surrounding alveolar bone to prevent stress shielding; the bottom must form a good bone bond with the surrounding alveolar bone to stabilize the implant. Current dental implants are uniform modulus implants that fail to accurately mimic the structure, function, and aesthetic gradient from the neck to the root.

[0004] Therefore, it is an urgent problem to provide a bionic dental implant with antibacterial, neck-to-root mechanical (elastic modulus), aesthetic gradient, osteogenic and antibacterial properties. Summary of the invention

[0005] The purpose of the present invention is to provide a bionic polyetheretherketone dental implant material and a preparation method thereof, so as to solve the problem that the existing dental implants fail to accurately biomimize the structure, function and aesthetic gradient from the neck to the root.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a bionic polyetheretherketone dental implant material, comprising the following steps:

[0008] The first polyetheretherketone and the first glass fiber are first mixed in the first ethanol, and first dried after the first mixing to obtain a first composite powder; the content of the first glass fiber in the first composite powder is 15wt%;

[0009] The second polyetheretherketone, the second glass fiber and the second modified material are mixed in the second ethanol for a second time, and after the second mixing, a second drying is performed to obtain a second composite powder; the content of the second glass fiber in the second composite powder is 12wt%; the content of the second modified material in the second composite powder is 0.4wt%;

[0010] The third polyetheretherketone, the third glass fiber and the third modified material are mixed in a third ethanol for a third time, and after the third mixing, dried for a third time to obtain a third composite powder; the content of the third glass fiber in the third composite powder is 9wt%; the content of the third modified material in the third composite powder is 0.8wt%;

[0011] The fourth polyetheretherketone, the fourth glass fiber and the fourth modified material are mixed in a fourth ethanol, and after the fourth mixing, a fourth drying is performed to obtain a fourth composite powder; the content of the fourth glass fiber in the fourth composite powder is 6wt%; the content of the fourth modified material in the fourth composite powder is 1.2wt%;

[0012] The fifth polyetheretherketone, the fifth glass fiber and the fifth modified material are mixed in the fifth ethanol, and after the fifth mixing, they are dried to obtain a fifth composite powder; the content of the fifth glass fiber in the fifth composite powder is 3wt%; the content of the fifth modified material in the fifth composite powder is 1.6wt%;

[0013] The sixth polyetheretherketone and the sixth modified material are mixed in the sixth ethanol for the sixth time, and after the sixth mixing, they are dried for the sixth time to obtain a sixth composite powder; the content of the sixth modified material in the sixth composite powder is 2 wt %;

[0014] The first composite powder, the second composite powder, the third composite powder, the fourth composite powder, the fifth composite powder, and the sixth composite powder are respectively pressed to obtain a first composite powder disk, a second composite powder disk, a third composite powder disk, a fourth composite powder disk, a fifth composite powder disk, and a sixth composite powder disk;

[0015] The first composite powder disk, the second composite powder disk, the third composite powder disk, the fourth composite powder disk, the fifth composite powder disk, and the sixth composite powder disk are stacked in order from top to bottom, and vacuum hot pressed to obtain a polyetheretherketone composite material blank;

[0016] Designing a digital model of a dental implant, then performing function modeling to obtain an implant model, cutting a blank of a polyetheretherketone composite material according to the designed implant model using CAD / CAM to obtain a bionic polyetheretherketone dental implant material;

[0017] The second modified material, the third modified material, the fourth modified material, the fifth modified material and the sixth modified material are independently michelene, silicene, two-dimensional MOF, black scale, metal oxide or transition metal sulfide.

[0018] Preferably, in the method for preparing the bionic polyetheretherketone dental implant material, the D of the first polyetheretherketone, the second polyetheretherketone, the third polyetheretherketone, the fourth polyetheretherketone, the fifth polyetheretherketone, and the sixth polyetheretherketone is 50 The independent one is 30~80μm.

[0019] Preferably, in the above-mentioned method for preparing a bionic polyetheretherketone dental implant material, the diameters of the first glass fiber, the second glass fiber, the third glass fiber, the fourth glass fiber, and the fifth glass fiber are independently 5 to 20 μm; the lengths of the first glass fiber, the second glass fiber, the third glass fiber, the fourth glass fiber, and the fifth glass fiber are independently 50 to 200 μm.

[0020] Preferably, in the above-mentioned method for preparing a bionic polyetheretherketone dental implant material, the temperatures of the first mixing, the second mixing, the third mixing, the fourth mixing, the fifth mixing and the sixth mixing are independently 20 to 30°C, and the times of the first mixing, the second mixing, the third mixing, the fourth mixing, the fifth mixing and the sixth mixing are independently 1 to 3 hours.

[0021] Preferably, in the above-mentioned method for preparing a bionic polyetheretherketone dental implant material, the thicknesses of the first composite powder disk, the second composite powder disk, the third composite powder disk, the fourth composite powder disk, the fifth composite powder disk and the sixth composite powder disk are independently 2 to 4 mm.

[0022] Preferably, in the above method for preparing a bionic polyetheretherketone dental implant material, the temperature of the vacuum hot pressing is 350-380° C., and the time of the vacuum hot pressing is 0.5-1 h.

[0023] The invention also provides a bionic polyetheretherketone dental implant material prepared by a preparation method of the bionic polyetheretherketone dental implant material.

[0024] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) Establish a mechanical bionic polyetheretherketone dental implant with a gradient change of elastic modulus from high to low from the neck to the root. Use glass fiber for mechanical reinforcement and modified materials for biological modification, in the order of gradually weakening mechanics and gradually increasing biological activity from the neck to the root.

[0026] (2) Establish an aesthetic bionic polyetheretherketone dental implant with a gradient color change from light to dark from the neck to the root.

[0027] (3) Polyetheretherketone is a hydrophobic material, and the added modified material is a hydrophilic material. Therefore, the hydrophilicity of the modified polyetheretherketone composite material is enhanced, and the hydrophilicity gradually increases with the increase of the content. Theoretically, as the hydrophilicity increases, the osteogenesis effect will also increase, thereby establishing a functional bionic polyetheretherketone dental implant with gradually increasing hydrophilicity and osteogenesis from the neck to the root.

[0028] (4) An antibacterial polyetheretherketone dental implant with photothermal sterilization properties was established. The added bio-modified material has strong absorption of near-infrared and can convert light energy into heat energy. The implant was irradiated with 808nm near-infrared laser for 5 minutes, and the antibacterial effect against Escherichia coli and Staphylococcus aureus increased with the increase of the content of biological additives.

[0029] (5) After implantation, the modified material added in the present invention will gradually degrade over time to form porous polyetheretherketone, which is conducive to further cell growth and improves bone bonding efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required to be used in the description of the embodiments or the prior art are briefly introduced below.

[0031] Figure 1 is a schematic diagram of the bionic polyetheretherketone dental implant material prepared in Example 1;

[0032] Figure 2 The hydrophilic properties of the first composite powder disk, the second composite powder disk, the third composite powder disk, the fourth composite powder disk, the fifth composite powder disk, and the sixth composite powder disk in Example 1;

[0033] Figure 3 The antibacterial properties of the first composite powder disk, the second composite powder disk, the third composite powder disk, the fourth composite powder disk, the fifth composite powder disk, and the sixth composite powder disk in Example 1. DETAILED DESCRIPTION

[0034] The present invention provides a method for preparing a bionic polyetheretherketone dental implant material, comprising the following steps:

[0035] The first polyetheretherketone and the first glass fiber are first mixed in the first ethanol, and first dried after the first mixing to obtain a first composite powder; the content of the first glass fiber in the first composite powder is 15wt%;

[0036] The second polyetheretherketone, the second glass fiber and the second modified material are mixed in the second ethanol for a second time, and after the second mixing, a second drying is performed to obtain a second composite powder; the content of the second glass fiber in the second composite powder is 12wt%; the content of the second modified material in the second composite powder is 0.4wt%;

[0037] The third polyetheretherketone, the third glass fiber and the third modified material are mixed in a third ethanol for a third time, and after the third mixing, dried for a third time to obtain a third composite powder; the content of the third glass fiber in the third composite powder is 9wt%; the content of the third modified material in the third composite powder is 0.8wt%;

[0038] The fourth polyetheretherketone, the fourth glass fiber and the fourth modified material are mixed in a fourth ethanol, and after the fourth mixing, a fourth drying is performed to obtain a fourth composite powder; the content of the fourth glass fiber in the fourth composite powder is 6wt%; the content of the fourth modified material in the fourth composite powder is 1.2wt%;

[0039] The fifth polyetheretherketone, the fifth glass fiber and the fifth modified material are mixed in the fifth ethanol, and after the fifth mixing, they are dried to obtain a fifth composite powder; the content of the fifth glass fiber in the fifth composite powder is 3wt%; the content of the fifth modified material in the fifth composite powder is 1.6wt%;

[0040] The sixth polyetheretherketone and the sixth modified material are mixed in the sixth ethanol for the sixth time, and after the sixth mixing, they are dried for the sixth time to obtain a sixth composite powder; the content of the sixth modified material in the sixth composite powder is 2 wt %;

[0041] The first composite powder, the second composite powder, the third composite powder, the fourth composite powder, the fifth composite powder, and the sixth composite powder are respectively pressed to obtain a first composite powder disk, a second composite powder disk, a third composite powder disk, a fourth composite powder disk, a fifth composite powder disk, and a sixth composite powder disk;

[0042] The first composite powder disk, the second composite powder disk, the third composite powder disk, the fourth composite powder disk, the fifth composite powder disk, and the sixth composite powder disk are stacked in order from top to bottom, and vacuum hot pressed to obtain a polyetheretherketone composite material blank;

[0043] A digital model of a dental implant is designed, and then the implant model is obtained by performing function modeling. The polyetheretherketone composite material blank is cut according to the designed implant model using CAD / CAM to obtain a bionic polyetheretherketone dental implant material.

[0044] In the present invention, the second modified material, the third modified material, the fourth modified material, the fifth modified material and the sixth modified material are independently preferably michelene, silicene, two-dimensional MOF, black scale, metal oxide or transition metal sulfide, further preferably michelene, silicene, two-dimensional MOF or black scale, more preferably michelene or black phosphorus; the modified material has antibacterial and osteogenic properties.

[0045] In the present invention, the D of the first polyetheretherketone, the second polyetheretherketone, the third polyetheretherketone, the fourth polyetheretherketone, the fifth polyetheretherketone, and the sixth polyetheretherketone is 50 The thickness of each of them is preferably 30 to 80 μm, more preferably 40 to 60 μm, and even more preferably 50 to 55 μm.

[0046] In the present invention, the diameters of the first glass fiber, the second glass fiber, the third glass fiber, the fourth glass fiber, and the fifth glass fiber are independently preferably 5 to 20 μm, more preferably 8 to 15 μm, and more preferably 12 to 13 μm; the lengths of the first glass fiber, the second glass fiber, the third glass fiber, the fourth glass fiber, and the fifth glass fiber are independently preferably 50 to 200 μm, more preferably 80 to 160 μm, and more preferably 100 to 150 μm.

[0047] In the present invention, the usage ratio of the first ethanol to the first polyetheretherketone is preferably 2-4 mL:1 g, more preferably 2.5-3.5 mL:1 g, and more preferably 2.8-3 mL:1 g.

[0048] In the present invention, the usage ratio of the second ethanol to the second polyetheretherketone is preferably 2-4 mL:1 g, more preferably 2.5-3.5 mL:1 g, and even more preferably 2.8-3 mL:1 g.

[0049] In the present invention, the usage ratio of the third ethanol to the third polyetheretherketone is preferably 2-4 mL:1 g, more preferably 2.5-3.5 mL:1 g, and more preferably 2.8-3 mL:1 g.

[0050] In the present invention, the usage ratio of the fourth ethanol to the fourth polyetheretherketone is preferably 2-4 mL:1 g, more preferably 2.5-3.5 mL:1 g, and even more preferably 2.8-3 mL:1 g.

[0051] In the present invention, the usage ratio of the fifth ethanol to the fifth polyetheretherketone is preferably 2-4 mL:1 g, more preferably 2.5-3.5 mL:1 g, and even more preferably 2.8-3 mL:1 g.

[0052] In the present invention, the usage ratio of the sixth ethanol to the sixth polyetheretherketone is preferably 2-4 mL:1 g, more preferably 2.5-3.5 mL:1 g, and even more preferably 2.8-3 mL:1 g.

[0053] In the present invention, the temperature of the first mixing, the second mixing, the third mixing, the fourth mixing, the fifth mixing and the sixth mixing is preferably 20-30°C, more preferably 22-28°C, more preferably 24-25°C; the mixing time is preferably 1-3h, more preferably 1.5-2.5h, more preferably 2h.

[0054] In the present invention, the steps of independently filtering after the first mixing, the second mixing, the third mixing, the fourth mixing, the fifth mixing and the sixth mixing further include filtering.

[0055] In the present invention, the temperatures of the first drying, second drying, third drying, fourth drying, fifth drying and sixth drying are independently preferably 60-80°C, further preferably 65-75°C, and more preferably 68-70°C; the times of the first drying, second drying, third drying, fourth drying, fifth drying and sixth drying are independently preferably 3-5h, further preferably 3.5-4.5h, and more preferably 4h.

[0056] In the present invention, the thickness of the first composite powder disk, the second composite powder disk, the third composite powder disk, the fourth composite powder disk, the fifth composite powder disk, and the sixth composite powder disk are preferably independently 2 to 4 mm, more preferably 2.5 to 3.5 mm, and more preferably 3 mm.

[0057] In the present invention, the temperature of the vacuum hot pressing is preferably 350-380°C, more preferably 360-370°C, and more preferably 350°C; the time of the vacuum hot pressing is preferably 0.5-1h, more preferably 0.5-0.75h, and more preferably 0.5h.

[0058] The invention also provides a bionic polyetheretherketone dental implant prepared by a preparation method of the bionic polyetheretherketone dental implant.

[0059] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0060] In the following Example 1, the D of the polyetheretherketone powder is 50 is 50μm; the diameter of the glass fiber is 5μm, and the length of the glass fiber is 80μm; Michaelene (Ti 3 C 2 T X ) flakes were purchased from Xianfeng Nano, CAS: 12363-89-2.

[0061] In the following Example 2, the D of the polyetheretherketone powder is 50 The diameter of the glass fiber is 12 μm, and the length of the glass fiber is 120 μm. The black scale was purchased from Xianfeng Nano, CAS: 7723-14-0.

[0062] Example 1

[0063] 100 g of polyetheretherketone powder and glass fiber were mixed in 200 mL of ethanol, and the mixture was magnetically stirred at 25° C. for 2 hours, followed by filtration and drying at 70° C. for 4 hours to obtain a first composite powder; the content of the glass fiber in the first composite powder was 15 wt %;

[0064] 100g of polyetheretherketone powder, glass fiber, and methacrylate (Ti 3 C 2 T X ) flakes were mixed in 200 mL of ethanol, magnetically stirred at 25°C for 2 hours, filtered, and dried at 70°C for 4 hours to obtain a second composite powder; the content of glass fiber in the second composite powder was 12 wt%; the content of mikhene (Ti 3 C 2 T X ) flake content is 0.4wt%;

[0065] 100g of polyetheretherketone powder, glass fiber, and methacrylate (Ti 3 C 2 T X ) flakes were mixed in 200 mL of ethanol, magnetically stirred at 25°C for 2 hours, filtered, and dried at 70°C for 4 hours to obtain a third composite powder; the content of glass fiber in the third composite powder was 9 wt%; the content of mikhene (Ti 3 C 2 T X ) flake content is 0.8wt%;

[0066] 100g of polyetheretherketone powder, glass fiber, and methacrylate (Ti 3 C 2 T X) flakes were mixed in 200 mL of ethanol, magnetically stirred at 25°C for 2 hours, filtered, and dried at 70°C for 4 hours to obtain a fourth composite powder; the content of glass fiber in the fourth composite powder was 6 wt%; the content of mikhene (Ti 3 C 2 T X ) flakes content is 1.2wt%;

[0067] 100g of polyetheretherketone powder, glass fiber, and methacrylate (Ti 3 C 2 T X ) flakes were mixed in 200 mL of ethanol, magnetically stirred at 25°C for 2 hours, filtered, and dried at 70°C for 4 hours to obtain a fifth composite powder; the content of glass fiber in the fifth composite powder was 3 wt%; the content of mikhene (Ti 3 C 2 T X ) flake content is 1.6wt%;

[0068] 100g of polyetheretherketone powder, michelene (Ti 3 C 2 T X ) flakes were mixed in 200 mL of ethanol, magnetically stirred at 25°C for 2 hours, filtered, and dried at 70°C for 4 hours to obtain the sixth composite powder; the sixth composite powder contained mikhene (Ti 3 C 2 T X ) the content of flakes is 2wt%;

[0069] The first composite powder, the second composite powder, the third composite powder, the fourth composite powder, the fifth composite powder, and the sixth composite powder are pressed respectively to obtain a first composite powder disk with a thickness of 3 mm, a second composite powder disk with a thickness of 3 mm, a third composite powder disk with a thickness of 3 mm, a fourth composite powder disk with a thickness of 3 mm, a fifth composite powder disk with a thickness of 3 mm, and a sixth composite powder disk with a thickness of 3 mm;

[0070] The first composite powder disk, the second composite powder disk, the third composite powder disk, the fourth composite powder disk, the fifth composite powder disk, and the sixth composite powder disk are stacked in sequence, with the sixth composite powder disk being the bottom layer and the first composite powder disk being the top layer, and then vacuum hot pressing is performed at 350° C. for 30 minutes to obtain a polyetheretherketone composite material blank;

[0071] A digital model of a dental implant is designed, and then the implant model is obtained by performing function modeling. The polyetheretherketone composite material blank is cut according to the designed implant model using CAD / CAM to obtain a bionic polyetheretherketone dental implant material.

[0072] The schematic diagram of the biomimetic polyetheretherketone dental implant material prepared in Example 1 is as follows Figure 1 As shown in Figure 1, the aesthetic bionic polyetheretherketone dental implant material has a color gradient from light to dark from the neck to the root.

[0073] The hydrophilic properties of the first composite powder disk, the second composite powder disk, the third composite powder disk, the fourth composite powder disk, the fifth composite powder disk, and the sixth composite powder disk in Example 1 are as follows: Figure 2 As shown. Figure 2 It can be seen that polyetheretherketone is a hydrophobic material, and michelene is a hydrophilic material. The hydrophilicity of the modified polyetheretherketone composite material is enhanced, and the hydrophilicity gradually increases with the increase of michelene content. In theory, the effect of promoting osteogenesis will also increase with the increase of hydrophilicity.

[0074] The antibacterial properties of the first composite powder disk, the second composite powder disk, the third composite powder disk, the fourth composite powder disk, the fifth composite powder disk, and the sixth composite powder disk in Example 1 are as follows: Figure 3 As shown. Figure 3 It can be seen that when the implant material is irradiated with 808nm near-infrared laser for 5 minutes, the antibacterial effect against Escherichia coli and Staphylococcus aureus increases with the increase of the content of biological additives.

[0075] Example 2

[0076] 100 g of polyetheretherketone powder and glass fiber were mixed in 250 mL of ethanol, magnetically stirred at 25° C. for 2 hours, filtered, and dried at 70° C. for 4 hours to obtain a first composite powder; the content of the glass fiber in the first composite powder was 15 wt %;

[0077] 100 g of polyetheretherketone powder, glass fiber and black scale were mixed in 250 mL of ethanol, and the mixture was magnetically stirred at 25° C. for 2 h, filtered, and dried at 70° C. for 4 h to obtain a second composite powder; the content of the glass fiber in the second composite powder was 12 wt %; the content of the black scale in the second composite powder was 0.4 wt %;

[0078] 100 g of polyetheretherketone powder, glass fiber and black scale were mixed in 250 mL of ethanol, and the mixture was magnetically stirred at 25° C. for 2 hours, and then filtered and dried at 70° C. for 4 hours to obtain a third composite powder; the content of the glass fiber in the third composite powder was 9 wt %; the content of the black scale in the third composite powder was 0.8 wt %;

[0079] 100 g of polyetheretherketone powder, glass fiber and black scale were mixed in 250 mL of ethanol, and the mixture was magnetically stirred at 25° C. for 2 h, and then filtered and dried at 70° C. for 4 h to obtain a fourth composite powder; the content of the glass fiber in the fourth composite powder was 6 wt %; the content of the black scale in the fourth composite powder was 1.2 wt %;

[0080] 100 g of polyetheretherketone powder, glass fiber and black scale were mixed in 250 mL of ethanol, and the mixture was magnetically stirred at 25° C. for 2 hours, and then filtered and dried at 70° C. for 4 hours to obtain a fifth composite powder; the content of the glass fiber in the fifth composite powder was 3 wt %; the content of the black scale in the fifth composite powder was 1.6 wt %;

[0081] 100 g of polyetheretherketone powder and black scale were mixed in 250 mL of ethanol, magnetically stirred at 25° C. for 2 h, filtered, and dried at 70° C. for 4 h to obtain a sixth composite powder; the content of black scale in the sixth composite powder was 2 wt %;

[0082] The first composite powder, the second composite powder, the third composite powder, the fourth composite powder, the fifth composite powder, and the sixth composite powder are pressed respectively to obtain a first composite powder disk with a thickness of 3 mm, a second composite powder disk with a thickness of 3 mm, a third composite powder disk with a thickness of 3 mm, a fourth composite powder disk with a thickness of 3 mm, a fifth composite powder disk with a thickness of 3 mm, and a sixth composite powder disk with a thickness of 3 mm;

[0083] The first composite powder disk, the second composite powder disk, the third composite powder disk, the fourth composite powder disk, the fifth composite powder disk, and the sixth composite powder disk are stacked in sequence, with the sixth composite powder disk being the bottom layer and the first composite powder disk being the top layer, and then vacuum hot pressing is performed at 360° C. for 40 minutes to obtain a polyetheretherketone composite material blank;

[0084] A digital model of a dental implant is designed, and then the implant model is obtained by performing function modeling. The polyetheretherketone composite material blank is cut according to the designed implant model using CAD / CAM to obtain a bionic polyetheretherketone dental implant material.

[0085] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a bionic polyetheretherketone dental implant material, characterized in that: The following steps are involved: The first polyetheretherketone and the first glass fiber are first mixed in the first ethanol, and first dried after the first mixing to obtain a first composite powder; the content of the first glass fiber in the first composite powder is 15wt%; The second polyetheretherketone, the second glass fiber and the second modified material are mixed in the second ethanol for a second time, and after the second mixing, a second drying is performed to obtain a second composite powder; the content of the second glass fiber in the second composite powder is 12wt%; the content of the second modified material in the second composite powder is 0.4wt%; The third polyetheretherketone, the third glass fiber and the third modified material are mixed in a third ethanol for a third time, and after the third mixing, dried for a third time to obtain a third composite powder; the content of the third glass fiber in the third composite powder is 9wt%; the content of the third modified material in the third composite powder is 0.8wt%; The fourth polyetheretherketone, the fourth glass fiber and the fourth modified material are mixed in a fourth ethanol, and after the fourth mixing, a fourth drying is performed to obtain a fourth composite powder; the content of the fourth glass fiber in the fourth composite powder is 6wt%; the content of the fourth modified material in the fourth composite powder is 1.2wt%; The fifth polyetheretherketone, the fifth glass fiber and the fifth modified material are mixed in the fifth ethanol, and after the fifth mixing, they are dried to obtain a fifth composite powder; the content of the fifth glass fiber in the fifth composite powder is 3wt%; the content of the fifth modified material in the fifth composite powder is 1.6wt%; The sixth polyetheretherketone and the sixth modified material are mixed in the sixth ethanol for the sixth time, and after the sixth mixing, they are dried for the sixth time to obtain a sixth composite powder; the content of the sixth modified material in the sixth composite powder is 2 wt %; The first composite powder, the second composite powder, the third composite powder, the fourth composite powder, the fifth composite powder, and the sixth composite powder are respectively pressed to obtain a first composite powder disk, a second composite powder disk, a third composite powder disk, a fourth composite powder disk, a fifth composite powder disk, and a sixth composite powder disk; The first composite powder disk, the second composite powder disk, the third composite powder disk, the fourth composite powder disk, the fifth composite powder disk, and the sixth composite powder disk are stacked in order from top to bottom, and vacuum hot pressed to obtain a polyetheretherketone composite material blank; Designing a digital model of a dental implant, then performing function modeling to obtain an implant model, cutting a blank of a polyetheretherketone composite material according to the designed implant model using CAD / CAM to obtain a bionic polyetheretherketone dental implant material; The second modified material, the third modified material, the fourth modified material, the fifth modified material and the sixth modified material are independently michelene, silicene, two-dimensional MOF, black scale, metal oxide or transition metal sulfide.

2. The method for preparing the bionic polyetheretherketone dental implant material according to claim 1, characterized in that: The D of the first polyetheretherketone, the second polyetheretherketone, the third polyetheretherketone, the fourth polyetheretherketone, the fifth polyetheretherketone and the sixth polyetheretherketone 50 The independent one is 30~80μm.

3. The method for preparing the bionic polyetheretherketone dental implant material according to claim 2, characterized in that: The diameters of the first glass fiber, the second glass fiber, the third glass fiber, the fourth glass fiber, and the fifth glass fiber are independently 5 to 20 μm; the lengths of the first glass fiber, the second glass fiber, the third glass fiber, the fourth glass fiber, and the fifth glass fiber are independently 50 to 200 μm.

4. The method for preparing the bionic polyetheretherketone dental implant material according to claim 3, characterized in that: The temperatures of the first mixing, the second mixing, the third mixing, the fourth mixing, the fifth mixing and the sixth mixing are independently 20-30° C., and the times of the first mixing, the second mixing, the third mixing, the fourth mixing, the fifth mixing and the sixth mixing are independently 1-3 hours.

5. The method for preparing the bionic polyetheretherketone dental implant material according to claim 3 or 4, characterized in that: The thickness of the first composite powder disk, the second composite powder disk, the third composite powder disk, the fourth composite powder disk, the fifth composite powder disk, and the sixth composite powder disk are independently 2 to 4 mm.

6. The method for preparing the bionic polyetheretherketone dental implant material according to claim 5, characterized in that: The temperature of the vacuum hot pressing is 350-380° C., and the time of the vacuum hot pressing is 0.5-1 h.

7. The bionic polyetheretherketone dental implant material obtained by the preparation method of the bionic polyetheretherketone dental implant material according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Technology for manufacturing compound planting tooth

    CN103479443A

  • Preparation method and application of carbon fiber reinforced polymer-based composite material

    CN105599321A

  • Polyethylene powder, sintered porous sheet, absorption buffer material and battery film

    CN109422918A

  • Method of recovering optical disk substrate and optical disk substrate recovering apparatus

    EP1040900A1

  • Composite material comprising fibrous organic material and fibrous calcium phosphate

    EP1588724A2

Cited By

  • Bionic polyetheretherketone dental implant material and method for preparing same

    WO2026066051A1